Attitude of Young Adults towards New Luxury Brand Positioning in Chinese Coffee Market - Gan, Lu (2011)
The aim of this dissertation is to investigate the perception of young adults – age between 18 and 25 – towards new luxury brand positioning in the coffee market, in order to know how new luxury brand positioning influences young adults and what elements lead them to new luxury brands. Similar phrases to new luxury brand positioning are Masstige positioning and affordable luxury. The wants of luxury products and relatively low price makes the need for this research. This dissertation was based on a review of related literatures and qualitative research through 2 focus groups. The findings underline that new luxury brand positioning strategy works for young adults, and it can influence them on their loyalty level of the brand. Furthermore, the research shows that the key elements that lead young adults to new luxury brands are service environment, intangible associations and rational benefits. The main conclusion to be drawn from this dissertation is that the elements that lead consumers tonew luxury brand positioning can be the vital factors when marketing department building brand positioning strategies so as to improve the loyalty level of consumers to the brand. Keywords: new luxury, Masstige positioning, affordable luxury, young adults, coffee.